Techinical assistance with traditional chinese medicine in primary care service of health - Fortes Ribeiro, Andreia; Terribile, Dhiane; Mocelin, Cheila; Ceratto, Paola Cristina; Curioletti, Regina Maria; Bagatini, Margarete Dulce; Ignacio, Zuleide Maria (Guará Journal, 2025)
Following the publication of the National Policy on Integrative and Complementary Practices, the need arose to create spaces for dialogue and dissemination of holistic therapies for its implementation. This paper reports on an experience of extending services using Traditional Chinese Medicine in a SUS unit. Based on the results obtained to date, it can be inferred that the continuous inclusion of ICT in SUS primary care services can be an important tool for increasing the well-being and quality of life of the patients served, directly contributing to health promotion strategies.
Keywords: PNPIC; Chinese Traditional Medicine; SUS; Primary Care